1984
DOI: 10.1111/j.1768-322x.1984.tb00200.x
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscope cytochemistry of normal and leukaemic leukocytes

Abstract: Backscattered Electron Imaging (BEI) is a particular technique which permits to study cytochemical reactions with the Scanning Electron Microscope (SEM). The BEI data pertaining to specific enzymatic activities can be directly correlated to the surface morphology of each individual cell. Leukocytes from 5 normal individuals, 14 patients with acute nonlymphoblastic leukaemia (ANLL), 7 patients with chronic myeloid leukaemia (CML) and 3 patients with acute lymphoblastic leukaemia (ALL) were studied for myelopero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…We have recently demonstrated that gold particles of 13 nm in diameter can be resolved in the BE1 mode (JEOL JSM 840, with a LaBe cathode; Soligo and de Harven, 1985). Observations of immunogold labeling with the transmission electron microscope have already demonstrated that, by using gold particles of different sizes with a judicious choice of ligand, doubIe labeling experiments can be carried out (Bendayan, 1982).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…We have recently demonstrated that gold particles of 13 nm in diameter can be resolved in the BE1 mode (JEOL JSM 840, with a LaBe cathode; Soligo and de Harven, 1985). Observations of immunogold labeling with the transmission electron microscope have already demonstrated that, by using gold particles of different sizes with a judicious choice of ligand, doubIe labeling experiments can be carried out (Bendayan, 1982).…”
Section: Resultsmentioning
confidence: 98%
“…It makes the labeling of those antigens that are excessively denatured by 0.2% glutaraldehyde (10 min) impossible. Our experience has shown that many surface antigens expressed on the surface of human leukocytes resist glutaraldehyde fixation under these conditions (Soligo and de Harven, 1985). It probably would be an oversimplification, however, to classify surface antigens in only two groups, "resistant" and "nonresistant."…”
Section: Resultsmentioning
confidence: 98%
“…Thus, BE rather than SE images must be studied for counting gold-labelled antigenic sites, and small particles must be used to minimize steric hindrance. We have recently shown that 20 nm (de Harven et al, 1984) and even 13 nm (Soligo & de Harven, 1985) gold particles can be resolved, using the solid state BE detector of a JEOL JSM 840 scanning electron microsocope equipped with a lanthanum hexaboride (LaB,) cathode. Although carbon coating does not completely prevent electrostatic charge, it permits accurate counting of gold particles in the BE1 mode of the SEM.…”
Section: Instrumental Factorsmentioning
confidence: 99%
“…The choice o f accelerating voltage does not seem to be a very critical factor, although the resolution o f 13 n m gold particles (Soligo & de Harven, 1985) was achieved using 35 kV and the smallest available probe current ( 1 x 1 0 " A). The accelerating voltage and probe current must be adjusted for each sample to minimize the diffuse non-specific backscattered electron signal emitted by the irradiated cells.…”
Section: Instrumental Factorsmentioning
confidence: 99%
“…Despite a large body of evidence using optical imaging for the characterization of zebrafish and Xenopus embryos on chip‐based devices, no attempts have been so far made to interface microfabricated chip‐based technologies with scanning electron microscopy (SEM). Because the SEM imaging is based on electron scattering at the surface rather than electron transmission, the analysis is fast and large amounts of samples can be analysed with a great depth of view . Such images are particularly appealing for small model organisms' morphological analysis by providing detailed 3D surface topographical information and yielding more information than the flat or reconstructed 3D images usually produced by confocal imaging.…”
mentioning
confidence: 99%